The Mexican Revolution in Chicago : immigration politics from the early twentieth century to the Cold War - Flores, John H., 1977- (Latinos in Chicago and Midwest Series., 2018)
"This project examines the diverse political culture of Mexican immigrants, the formation and efficacy of immigrant-led transnational organizations, and the variables that affect immigrant assimilation through a history of the Mexican immigrant community of metropolitan Chicago during the first half of the twentieth century. John Flores presents a narrative that revolves around the lives of immigrant community leaders, who are characterized as members of a "revolutionary generation." These immigrants include men and women, white-collar professionals, and blue-collar laborers who subscribed to a passionate sense of Mexican national identity that derived from their experience and understanding of the Mexican Revolution (1910-20), a civil war fought by diverse factions. After settling in the Chicago area, these Mexican nationalists formed liberal, conservative, and radical transnational organizations that continued commitments first initiated in Mexico. They also joined settlement houses, labor unions, and Catholic and Protestant Churches. Between the 1920s and the 1940s, the transplanted members of the diverse and divergent revolutionary generation competed to shape the identities and influence the political perspectives of the Mexicans residing within the United States. At a time of widespread interest in Mexican assimilation, this book attends to reasons why some Mexicans became American citizens and why others did not. In doing so, the project reveals how political events in Mexico and in the United States led Mexican liberals and radicals to reject US citizenship and conversely prodded Mexican conservatives to become Americans"--